The Role of Intellectual Capital in Improving the Competitive Advantage of Government Companies in the Country’s Future Vision: An Applied Study on Pharmaceutical Companies - Hussein, Ramez (The Arab Journal of Administration, 2023)
This study aimed to identify the role of intellectual capital (human capital, structural capital, relationship capital) in improving the competitive advantage of the government pharmaceutical companies. And the study was started from a major research question: How to achieve a competitive advantage for the pharmaceutical companies through intellectual capital. This study relied on descriptive analytical method in the presentation and analysis of data and information collected through secondary sources and the survey form where the number of (140) forms was distributed to the companies in question and the number of forms valid for statistical analysis (109) forms by (77.8%) This study found several findings, the most important of which are that there are medium trends towards human and structural capital variables in relation to the role of intellectual capital in improving the competitive advantage of the pharmaceutical companies in question. There is also a relationship between the application of intellectual capital trends and the competitive advantage of the pharmaceutical companies. The study recommended the need to focus on intellectual capital in its various dimensions and axes in order to achieve a competitive advantage in the domestic and external market of pharmaceutical companies.